Perspectives and Uses of the Electronic Health Record Among US Pediatricians: A National Survey. Issue 1 (January 2017) - Doberne, Julie W.; Redd, Travis; Lattin, Daniel; Yackel, Thomas R.; Eriksson, Carl O.; Mohan, Vishnu; Gold, Jeffrey A.; Ash, Joan S.; Chiang, Michael F.
Abstract : Little is known about how existing electronic health records (EHRs) influence the practice of pediatric medicine. A total of 808 pediatricians participated in a survey about workflows using the EHR. The EHR was the most commonly used source of initial patient information. Seventy-two percent reported requiring between 2 and 10 minutes to complete an initial review of the EHR. Several moderately severe information barriers were reported regarding the display of information in the EHR. Pediatricians acquire information about new patients from EHRs more often than any other source. EHRs play a critical role in pediatric care but require improved design and efficiency. Abstract : Supplemental Digital Content is Available in the Text.